2015
DOI: 10.1123/jpah.2013-0303
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Influences on Weight Status Among Impoverished Adolescents: Neighborhood Amenities for Physical Activity and State Laws for Physical Education Time Requirements

Abstract: This study emphasizes the potential significance of state laws on low SES groups to combat obesity; as well as the potential differential effects of local level factors, and alignment with policy goals for healthy weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, FLASHE did not assess school equipment or facilities, which might influence adolescent MVPA. 30 Adolescents were prompted to anchor on the area around their home, and not around their school, when thinking about different aspects of their neighborhood, consistent with the literature. 9 However, half of participants’ homes were located less than 2 miles from their school, with more than 25% living within 1 mile of their school.…”
Section: Discussionmentioning
confidence: 99%
“…However, FLASHE did not assess school equipment or facilities, which might influence adolescent MVPA. 30 Adolescents were prompted to anchor on the area around their home, and not around their school, when thinking about different aspects of their neighborhood, consistent with the literature. 9 However, half of participants’ homes were located less than 2 miles from their school, with more than 25% living within 1 mile of their school.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in the US on school policies report that state laws addressing physical education (PE) or additional PA opportunities (e.g., PA breaks) in school are related to higher adolescent PE participation, total PA, and lower rates of obesity (Morton et al, 2016; Cawley et al, 2007a; Oh et al, 2015; Perna et al, 2012; Taber et al, 2013). Youth who are physically active in school may also be more active after school hours (Dale et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, school SES has been shown to influence the impact of school nutrition legislation . Other studies have suggested that neighbourhood structural factors including amenities, poverty and racial composition may influence the impact of obesity prevention interventions .…”
Section: Discussionmentioning
confidence: 99%